Efektivitas Media Animasi Terhadap Pembelajaran Sprechfertigkeiten Pada Mahasiswa Prodi Pendidikan Bahasa Jerman - Simanjuntak, Tarida Alvina; Purba, Lydia; Saadoon, Abather (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The role of the educator in the implementation of learning plays a very important role as an innovator or agent of change in order to help students achieve learning goals, especially those related to the cultivation of skills, educators need to develop and create learning processes. One of the uses of technology that can be done is the use of animation media in learning. This study has a goal, namely to find out how student learning outcomes are in Sprechfertigkeiten learning using animation media. The research method used in this study is a quantitative descriptive experimental research. The subjects in the study were all students of the German Language Education Study Program Semester 3 (three) FKIP Nommensen Pematangsiantar HKBP University. The data collection technique in this study was a test of learning outcomes in accordance with the material taught in Sprechfertigkeiten learning. The procedure of this research is to test student learning outcomes to get differences in student learning outcomes after using animation media. The results of this study indicate the value of student learning outcomes in Sprechfertigkeiten learning with animation media. This can be seen from the increased average student learning outcomes (x = 83.90) compared to student learning outcomes before using digital learning applications (x = 70.27).